1997
DOI: 10.1590/s0006-87051997000100008
|View full text |Cite
|
Sign up to set email alerts
|

Iac-Maravilha, Iac-Una, Iac-Carioca Pyatã, Iac-Carioca Aruã, Iac-Carioca Akytã E Iac-Bico De Ouro: Novos Cultivares De Feijoeiro

Abstract: Os novos cultivares de feijoeiro, IAC-Una, IAC-Maravilha, IAC-Carioca Aruã, IAC-Carioca Pyatã, IAC-Carioca Akytã e IAC-Bico de Ouro são descritos, neste trabalho, quanto à origem, características da planta, vagem, semente e tegumento. `IAC-Una' e `IAC-Maravilha', ambos do grupo Preto, são resistentes aos patógenos da antracnose, ferrugem e mosaico comum. `IAC-Carioca Pyatã', `IAC-Carioca Akytã', `IAC-Carioca Aruã', do grupo Diversos, com sementes tipo Carioca, e `IAC-Bico de Ouro', do grupo do mesmo nome, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…In this sense, the commercial cultivars IPR-Curió, Carioca-MG, IAC-Akytã, IAC-Apuã, IAC-Aysó, IAC-Imperador, IAC-Pyatã, IAC-Formoso, IAC-Ybaté and IAC-Tybatã showed the greatest potential for use by Brazilian common bean breeding programs. These cultivars not only fulfilled the minimum requirements of any commercial cultivar [ 114 – 116 ], but also showed high resistance (i.e., score < 3) to the three races evaluated. Molecular evaluation by DAPC, estimated with the significant SNPs from GWAS, showed that these cultivars have the highest number of favorable alleles among the 18 genotypes grouped in terms of resistance pattern ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the commercial cultivars IPR-Curió, Carioca-MG, IAC-Akytã, IAC-Apuã, IAC-Aysó, IAC-Imperador, IAC-Pyatã, IAC-Formoso, IAC-Ybaté and IAC-Tybatã showed the greatest potential for use by Brazilian common bean breeding programs. These cultivars not only fulfilled the minimum requirements of any commercial cultivar [ 114 – 116 ], but also showed high resistance (i.e., score < 3) to the three races evaluated. Molecular evaluation by DAPC, estimated with the significant SNPs from GWAS, showed that these cultivars have the highest number of favorable alleles among the 18 genotypes grouped in terms of resistance pattern ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular evaluation by DAPC, estimated with the significant SNPs from GWAS, showed that these cultivars have the highest number of favorable alleles among the 18 genotypes grouped in terms of resistance pattern ( Fig 5 ). Among them, the cultivar IAC- Pyatã also showed high resistance to angular leaf spot in a recent study [ 69 ] and had the highest average yield among the 11 other commercial cultivars tested by Pompeu [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…flaccumfaciens isolado 2634 um caráter oligogênico (Valentini et al, 2011) e as fontes de resistên-cia para estas doenças serem de origens distintas. Segundo Pompeu (1997), o cultivar IAC-Carioca Aruã resulta de seleção feita em F 4 do cruzamento (10771.122) x [(H5380-41.A156) x (H5380-41.AB136)] e o cultivar IAC-Carioca Pyatã é proveniente de seleções realizadas na geração F 3 do cruzamento DOR41 x (10-3-1.TU1B1-2.10-9-1). Logo, para manter esta variabilidade, a seleção foi praticada em plantas com notas entre 1 e 4.…”
Section: Resultsunclassified
“…Algumas das linhagens avaliadas, H853-50-2 (IAC-Carioca Pyatã), H853-50-6 (IAC-Carioca Akytã), H8522-50-2 (IAC-Carioca Aruã) e H3886-52 (IAC-Maravilha), por suas produções médias de grãos, reação resistente aos agentes patogênicos da antracnose e vírus-do-mosaicocomum, coloração de sementes e porte ereto de planta, já foram lançadas e recomendadas como novas cultivares (Pompeu, 1997). A linhagem 51-1-1-1, em mistura com sua irmã 51-1-1-2 (IAC-Una) e H8557-54 (IAC-Bico de Ouro), pelas características acima mencionadas e pela coloração das sementes, preta e tipo bico-de-ouro, respectivamente, também foram lançadas e recomendadas no Estado de São Paulo (Pompeu, 1997).…”
Section: Resultsunclassified
“…A linhagem 51-1-1-1, em mistura com sua irmã 51-1-1-2 (IAC-Una) e H8557-54 (IAC-Bico de Ouro), pelas características acima mencionadas e pela coloração das sementes, preta e tipo bico-de-ouro, respectivamente, também foram lançadas e recomendadas no Estado de São Paulo (Pompeu, 1997). No entanto, a linhagem H8557-54, por sua baixa produção na épo-ca da seca, foi recomendada somente para as épocas das águas e de inverno.…”
Section: Resultsunclassified